Research on Evaluation Index of High Temperature Performance of Rubberized Asphalt Binder - Xie, Cheng; Luo, Junhui; Zeng, Lihao; Ren, Tianzeng; Liu, Haobin; Chen, Jiangcai (Frontiers in Materials, 2022)
The high-temperature rheological properties of rubberized asphalt and mixture were evaluated by frequency scanning, repeated creep recovery (RCR) test, temperature sweep test, Hamburg wheel tracking test (HWTT). Based on the Pearson correlation coefficient, the correlation of the mixture gradation and asphalt characteristics with the high-temperature stability of the mixture was analyzed. Finally, the gray correlation theory was applied to analyze the evaluation indexes of the high-temperature rheological properties of rubberized asphalt and mixture. The results show that the asphalt-stone ratio and the fractal dimension (Dc) of coarse aggregate have a significant correlation with the high-temperature performance of the mixture, and the mixture with a smaller asphalt-stone ratio and a higher percentage of coarse aggregate has a better high-temperature performance. The correlation degree of softening point, viscous stiffness modulus and permanent deformation with rubber-asphalt mixture is higher than 0.7, and are significantly higher than those of rotational viscosity at 180°C. Therefore, we recommend the use of permanent deformation, softening point, and viscous stiffness modulus to evaluate the high-temperature performance of rubberized asphalt mixture.